AKTIVITAS ENTOMOPATOGEN Serratia marcescens Bizio TERHADAP MORTALITAS LARVA KUMBANG KELAPA (Brontispa longissima) Gestro - Siti Ramla S. Kahar; Ani Hasan; Chairunnisa Lamangantjo (Jambura Edu Biosfer Journal, 2019)
Entomopathogen is one of the biological agents that infects the insects and can damage the body's metabolic system of insects. This objective of the study were to determine the entomopathogenic activity of S. marcescens on mortality of coconut leaf beetles larvae (B. longissima), and the time needed to reach LT50. The study used an experimental method with 6 treatments of varying S.marcescens volumes, consisting of A (distilled water as a control), B (5 ml), C (7.5 ml), D (10 ml), E (12.5 ml), and F (15 ml) with 4 replications. The data were analyzed using ANOVA and Probit LT50 test. The results showed that the volume of S.marcescens had an effect on mortality of coconut leaf beetle B. longissimi larvae. The best mortality rate at treatment E is 78% with the value of LT50 in treatment F is 42.15 hours. S.marcescens has entomopathogenic activity in coconut leaf beetles (B. longissima) Gestro larvae